Recent advances in porphyrin-based nanocomposites for effective targeted imaging and therapy - Rabiee, Navid; Yaraki, Mohammad Tavakkoli; Garakani, Soha Mokhtari; Garakani, Shima Mokhtari; Ahmadi, Sepideh; Lajevardi, Aseman; Bagherzadeh, Mojtaba; Rabiee, Mohammad; Tayebi, Lobat; Tahriri, Mohammadreza; Hamblin, Michael R. (Biomaterials, 2020)
Porphyrins are organic compounds that continue to attract much theoretical interest, and have been called the “pigments of life”. They have a wide role in photodynamic and sonodynamic therapy, along with uses in magnetic resonance, fluorescence and photoacoustic imaging. There is a vast range of porphyrins that have been isolated or designed, but few of them have real clinical applications. Due to the hydrophobic properties of porphyrins, and their tendency to aggregate by stacking of the planar molecules they are difficult to work with in aqueous media. Therefore encapsulating them in nanoparticles (NPs) or attachment to various delivery vehicles have been used to improve delivery characteristics. Porphyrins can be used in a composite designed material with properties that allow specific targeting, immune tolerance, extended tissue lifetime and improved hydrophilicity. Drug delivery, healing and repairing of damaged organs, and cancer theranostics are some of the medical uses of porphyrin-based nanocomposites covered in this review. Impact statement: Porphyrin nanocomposites are increasingly being used as rationally designed theranostic systems. This timely review gathers together diverse reports of these applications especially for cancer diagnosis and therapy.